Co-application of organic amendments and inorganic P increase maize growth and soil carbon, phosphorus availability in calcareous soil - Khan, Khuram Shehzad; Ali, Muhammad Moaaz; Naveed, Muhammad; Rehmani, Muhammad Ishaq Asif; Shafique, Muhammad Waleed; Ali, Hayssam M.; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; Feng, Gu (Frontiers in Environmental Science, 2022)
Phosphorus (P) constraint can be alleviated by increasing C inputs, which can help to improve crop production and P fertilizer use efficiency. However, the effects of different manures on soil microbial biomass P (MBP) and P fractions as well as C fractions in calcareous soils remain poorly understood. Soil MBP pool involves the P mineralization and immobilization processes, potentially changing P fractions and P availability. Therefore, the effects of different manures on soil microbial biomass (MBP, MBC) pool, P and C fractions and crop P utilization were evaluated in greenhouse experiments with maize plantation. Treatments included no manure (CK), poultry manure (PM), cow manure (CM), goat manure (GM), and mixed manure (MM), and three Pi rates; P0: 0 mg kg 1, P50: 50 mg kg 1 and P100: P100 mg kg 1 (P2O5). For plant growth comparison, crop physiological growth indices, shoot P contents and total P uptake were increased by PM and P100 as compared to other treatments. The PM with P100 significantly increased the plant growth by inducing P uptake ~ 18% compared with CK. The results exhibited that Pi (P100) combined with manure (PM) significantly (P<0.05) increased the soil physicochemical properties, i.e., 683.76 mg kg-1 total P, 21.5 mg kg 1 Olsen P, 4.26 mg kg 1 SOC, 2.41 mg kg 1 POC, as well as microbial biomass C and P increased by 152.84 mg kg 1 and 36.83 mg kg 1, respectively. Consequently, we concluded that PM with Pi (P100) application build up soil microbial biomass, which is more beneficial for promoting P utilization for maize.